Oil wealth and the fate of forest: a comparative study of eight tropical countries - Wunder, Sven (Routledge, 2003)
Oil production can damage rainforests, but this is just one side of a complicated story about the impact of oil on land use. This book a study of eight tropical oil-producing countries, examines the linkages between trade, macroeconomics and policies affecting the environment. In a balanced and comprehensive review, including a detailed assessment of land use in Cameroon, Ecuador, Gabon, Papua New Guinea and Venezuela, the author comes up with a counterintuitive suggestion: oil revenues often indirectly come to protect tropical forests. There are numerous implications for policy formulation to decide what can be done to diminish deforestation without jeopardising economic growth.